Faktor-Faktor Yang Mempengaruhi Penggunaan Penggumpal Anjuran Dalam Perbaikan Kualitas Bahan Olah Karet - Yanter Hutapea (Program Studi Agribisnis Universitas Sumatera Selatan, 2022)
Processing problems cause the low quality of raw rubber material (“bokar”) and farmers' income. Improving the quality of bokar must start from latex handling in the farm until the final processing stage. One way to improve the quality of bokar is the use of recommended coagulant. This study aims to determine the factors that influence the use of recommended coagulant in improving bokar processing by farmers. This study was conducted in Mulyaguna Village, Teluk Gelam Sub district, OKI Regency. Data collection was carried out from June to December 2021 through multiple visit surveys. The sample consisted of 24 people who used recommended coagulant and 21 people who did not use recommended coagulant. This study uses binary logistic regression analysis. The results showed that the factors that significantly influenced the use of recommended coagulant in improving the quality of bokar were the number of family members, the number of income sources and the number of farmer membership in the institutions.